Improving Learning Outcomes in Office Automation Subjects Through Development of Video-Based Media Learning Operating Microsoft Publisher 2010 - Irma Mastumasari; Wasiti -; Sulistyaningsih - (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2017)
The purpose of this research is to produce instructional media video-based operate Microsoft Publisher 2010 which is validated by experts for student at class X of Office Administration in SMKN 1 Malang through experimental class and control class. This study uses Research and Development research design (R & D) through 8 steps, namely: (1) research and information gathering early, (2) planning, (3) product development, (4) validation expert, (5) product revision, (6) the trial court (small groups), (7) the revision of the product, and (8) field trials (large group). Results of validation by material experts, media experts and 12 students, the media is expressed very valid and can be used. Based on t test, it is known that a significant difference between the average student learning outcomes experimental class and control class, so that learning media can be said to be effective for use in the learning process.